Perspectives about voiceprints - Hollien, Harry; Suneetha Didla , Grace (Journal of Indian Academy of Forensic Medicine, 2019)
Forensic literature often claims “voiceprints” as an acceptable way to carry out forensic speaker identification. However, that assertion does not seem valid. Many advances in the area of speaker identification (SI) have occurred during the past five decades. Hence, it would appear useful to provide both a historical review and current perspectives of the “voiceprint” issue. The review also discusses other more advanced approaches to speaker identification, and provides a brief overview of the efficacy and future prospects of these newer approaches to speaker identification.